Influence of spray drying temperatures and storage conditions on physical and functional properties of dried egg white. Issue 2 (25th January 2018) - Katekhong, Wattinee; Charoenrein, Sanguansri
ABSTRACT: This study investigated the effect of spray drying inlet temperatures (140, 160 and 180°C) and storage conditions (temperature; 25 and 40°C and storage period; 1 and 2 months) on the physical and functional properties of dried egg white. The results showed that the three inlet temperatures did not affect the color of the spray-dried egg white (SDEW) after drying. However, all SDEWs increased in yellow color after storage at 40°C. The solubility (%) of SDEW and gelling properties including gel hardness and water holding capacity of the gel samples were changed when the dried samples were stored, particularly for SDEW drying at 180°C. The changes in gelling properties of the SDEW were related to a decrease in the enthalpy of protein denaturation, an increase in exposed sulfhydryl (SH) contents, a decrease in the total SH contents and the occurrence of protein aggregation as shown by the sodium dodecyl sulfate-polyacrylamide gel electrophoresis pattern.